2018
DOI: 10.3390/ijerph15020375
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Examinations of Effects of Three-Level Green Exercise on Engagement with Nature and Physical Activity

Abstract: Green exercise can be classified into three levels based on engagement with nature. Although this classification was proposed more than a decade ago, few studies have investigated it since. The present study examined the effects of green exercise levels on engagement with nature and physical activity (PA) through a field experiment. A questionnaire was distributed to 95 students from a technology university in Central Taiwan to measure their level of engagement with nature in people-environment transactions, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…However, the exercise environment provides the area to facilitate this. Researchers Han and Wang (2018) [40] highlight that individuals who choose to shift focus away from the natural environment may not receive benefits from conducting green exercise. This may be reflected with the motivation subscale ‘psychological condition’ being ranked lowest between the three forms of green exercise within competitive sport participants.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exercise environment provides the area to facilitate this. Researchers Han and Wang (2018) [40] highlight that individuals who choose to shift focus away from the natural environment may not receive benefits from conducting green exercise. This may be reflected with the motivation subscale ‘psychological condition’ being ranked lowest between the three forms of green exercise within competitive sport participants.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the walking group demonstrated a significant decrease in the physical exhaustion subscale, whereas the golf condition in fact showed a non-significant increase. Researcher’s Han and Wang (2018) [29] raise an interesting point regarding attentional focus. They state if an individual exercising in nature shifts attentional focus away from the environment, the physical and psychological benefits may be removed.…”
Section: Discussionmentioning
confidence: 99%
“…Rogerson et al (2016) suggested “the need for identifying remaining gaps in green exercise where the focus on the activity is greater for example during games or sports” [18] (p. 12). This point was echoed by Han and Wang (2018) who stated, “green exercise studies need to investigate a range of physical activities, participants and environments.” [29] (p.12). In terms of the study design, researchers Bamberg, Hitchings and Latham (2018) [30] also highlight that future green exercise studies should look to use more qualitative research methods to increase understanding between the exercise and environment response.…”
Section: Introductionmentioning
confidence: 99%
“…As for studies focusing on the third level of green exercise (active participation and involvement with nature), emphasis has been placed on gardening activities, "nature experiences," and "outward bound experiences." Few studies have examined all three levels concurrently [26]. Only six studies [11,[27][28][29][30][31] have been published on this subject, which compared only the effects of two levels of green exercise, but not all three.…”
Section: Introductionmentioning
confidence: 99%
“…The third level of green exercise (active participation and involvement with nature) was also found to have a greater effect of stress restoration than the first level of green exercise (viewing nature) [30]. Furthermore, research on green exercise has rarely considered the degree of engagement with nature or empirically examined its effects on people [26], even though the degree of engagement with nature is the criterion of the categorization of three levels of green exercise. Therefore, the first objective of the present study was to examine the effects of all three levels of green exercise on people's psychological health to address the gap in the literature.…”
Section: Introductionmentioning
confidence: 99%